Control of microgrids - Guo, Zhen (Nanyang Technological University, 2021)
Battery energy storage is currently one of the most widely used and most promising energy storage methods in microgrids. The establishment of a reasonable battery model is of great significance to the study of its dynamic performance in microgrid operation. This project focused on analysing several models of different levels of complexity in lithium battery research, and established corresponding simulation models in MATLAB/Simulink. By accurately estimating the state of charge (SOC) of the lithium battery to prevent the battery from overcharging and over-discharging, and to ensure the safety and full use of the battery. By conducting multiple simulation experiments with different variables, and then combining with theoretical analysis, formula derivation and simulation results of the model in the discharge process, the dynamic characteristics of these equivalent circuit models were analysed. Finally, the Dynamic Equivalent Circuit Battery Model was integrated to the Simplified Model of a Small-Scale Micro-Grid. The simulation results have verified the rationality and effectiveness of the battery model.